Anti-microbial efficacy of garlic (Allium Sativum L.) extract as a root canal irrigant in endodontic treatment - Cahyani, Febriastuti; Farizaldi, Reisya Irfanny; Syafaati, Lailatul Maghfiroh; Hartanli, Audrey Luisa; Aryandhita, Amanda Paramitha Putri (Universitas Airlangga, 2023)
Background: Herbal medications are an effective alternative in dental endodontic treatment due to their antimicrobial, anti-inflammatory, and biocompatibility properties and thus they are more biocompatible and less cytotoxic. The antibacterial, antifungal, and antiviral properties of garlic (Allium sativum L.) support broad-spectrum activity against gram-positive and gram-negative organisms and effectiveness against multidrug-resistant organisms that are essential as endodontic materials. Purpose: The purpose of this literature review is to analyze how the antimicrobial efficacy of garlic (Allium sativum L.) extract can be used as a root canal irrigant in endodontic treatment. Review: The development of pulp and periapical disease involves high-intensity bacterial activity that proliferates and produces toxic side products such as organic acids. When crushed or minced, garlic releases allicin compounds through the enzymatic action of alliinase (cysteine sulfoxide lyase) on alliin. Allicin, organosulfur compounds, and antioxidant compounds in garlic extract can exert antimicrobial role by inhibiting the synthesis of pathogenic microorganisms, fighting the resulting infection, and working synergistically with other antimicrobial agents to increase the effectiveness of treatment against antibiotic- resistant bacterial infections. In comparison to other antimicrobial agents, a number of studies have shown that there is no significant difference between garlic extract and sodium hypochlorite (NaOCl) in exerting bactericidal effects against pathogenic bacteria. Other studies have also shown that garlic extract has good dentin penetration properties as well as ideal flow and wetting capabilities. Conclusion: Garlic (Allium sativum L.) extract has good antimicrobial efficacy, dentin penetration, as well as ideal properties of root canal irrigation in endodontic treatment